Improving the Quality of Financial Reports Using the Zahir Application at the Zet Chici Souvenir Center in Padang City - Ananda, Febryandhie; Meirina, Elsa; Hamdani Putra, Gerry; Rivandi, Muhammad; Umar, Desyani (Cahaya Pengabdian, 2024)
The purpose of this activity is so that MSME actors can prepare business proposals and be able to analyze financial statements so that MSMEs are realized as efficient, healthy and high-growth businesses, able to become the people's economic strength and make a great contribution to national economic development. The activity began with observation and correspondence through WA to find out the needs of Micro, Small and Medium Enterprises (MSMEs) Then it was carried out by delivering material related to Improving the Quality of Financial Reports Using the Zahir Application. Community Empowerment Activities for MSMEs Through Improving the Quality of Financial Reports Using the Zahir Application at the Zet Chici Souvenir Center were carried out in accordance with what was expected. This can be seen from the positive response of MSME actors. It is hoped that in the future similar training and mentoring activities can be held again in order to improve the knowledge and skills of MSME actors in compiling financial statements and analyzing financial statements in order to access capital in banking institutions and other financial institutions